A Look into Stem Cell Therapy: Exploring the Options for Treatment of Ischemic Stroke. (22nd October 2017) - Reis, Cesar; Wilkinson, Michael; Reis, Haley; Akyol, Onat; Gospodarev, Vadim; Araujo, Camila; Chen, Sheng; Zhang, John H.
Abstract : Neural stem cells (NSCs) offer a potential therapeutic benefit in the recovery from ischemic stroke. Understanding the role of endogenous neural stem and progenitor cells under normal physiological conditions aids in analyzing their effects after ischemic injury, including their impact on functional recovery and neurogenesis at the site of injury. Recent animal studies have utilized unique subsets of exogenous and endogenous stem cells as well as preconditioning with pharmacologic agents to better understand the best situation for stem cell proliferation, migration, and differentiation. These stem cell therapies provide a promising effect on stimulation of endogenous neurogenesis, neuroprotection, anti-inflammatory effects, and improved cell survival rates. Clinical trials performed using various stem cell types show promising results to their safety and effectiveness on reducing the effects of ischemic stroke in humans. Another important aspect of stem cell therapy discussed in this review is tracking endogenous and exogenous NSCs with magnetic resonance imaging. This review explores the pathophysiology of NSCs on ischemic stroke, stem cell therapy studies and their effects on neurogenesis, the most recent clinical trials, and techniques to track and monitor the progress of endogenous and exogenous stem cells.